CO extrusion in homogeneous gold catalysis: reactivity of gold acyl species generated through water addition to gold vinylidenes - Bucher, Janina; Stößer, Tim; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2014)
Herein, we describe a new gold-catalyzed decarbonylative indene synthesis. Synergistic σ,π-activation of diyne substrates leads to gold vinylidene intermediates, which upon addition of water are transformed into gold acyl species, a type of organogold compound hitherto only scarcely reported. The latter are shown to undergo extrusion of CO, an elementary step completely unknown for homogeneous gold catalysis. By tuning the electronic and steric properties of the starting diyne systems, this new reactivity could be exploited for the synthesis of indene derivatives in high yields.